Nichols, Brian (London, 2008)
2008 "Nichols, Brian", 2008, HistoryTalk Brian was born in Poplar in 1937. He passed the 11-plus and went to the local technical college and when he was 16 I got a job at Plessey as an apprentice engineer for 5 years.